Justice as a spiritual quest. Issue 3 (3rd July 2021) - Eze, Chielozona
ABSTRACT: This essay is based on the assumption that retributive justice fails to capture the immense riches of the human condition. Exploring the South African Truth and Reconciliation Commission (TRC), it argues that restorative justice must be seen as complementary to the retributive and other conceptions of justice. Restorative justice is presented here as a spiritual journey, one that is best grasped through the prism of Benjamin's spiritual elements of class struggles. Nelson Mandela understood, like Georg Friedrich Hegel, that even the Absolute Spirit, powerful as it is, achieves its goal through cunning. Spiritual quest is, however, much more than the cunning of the spirit; it is also love and human flourishing understood as inclusive projects.